2016
DOI: 10.1097/sih.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Simulation-Based Training Program for the Prehospital Professionals and Students on the Management of Middle East Respiratory Syndrome

Abstract: The training program was appropriate for both paramedic students and EMS providers. A positive educational climate was created. Because the main concerns of this study were awareness and preparedness, which required human interaction, the SP methodology was the optimal simulation modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Study characteristics are presented in table 3. A majority of the studies reported on learning interventions developed in response to EVD (n=24, 52%), eight studies were motivated by SARS (17%), [44][45][46][47][48][49][50][51] seven studies by H1N1 influenza (15%), [52][53][54][55][56][57][58] one study by MERS (2%) 59 and three studies were motivated by more than one disease. [60][61][62] Three studies were published in relation to COVID-19.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Study characteristics are presented in table 3. A majority of the studies reported on learning interventions developed in response to EVD (n=24, 52%), eight studies were motivated by SARS (17%), [44][45][46][47][48][49][50][51] seven studies by H1N1 influenza (15%), [52][53][54][55][56][57][58] one study by MERS (2%) 59 and three studies were motivated by more than one disease. [60][61][62] Three studies were published in relation to COVID-19.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Significant research has been done, and more is required, that is why this theme is converting from emerging to transversal. Research topics under this themes are related to the effect of infectious disease on descriptive of humans such as male, female, adults, old age, middle age, residents, foreigners and travelers such as discussed in [62] [64] , [16] , [65] , and [66] . This research theme cluster is represented by a communicable disease.…”
Section: Bibliometric Analysis and Visualizationmentioning
confidence: 99%
“…In concordance with the literature, donning and doffing played a significant role in infection acquisition, whether due to lack of knowledge of the correct sequence of steps for donning and doffing. [ 17 18 ] Another explanation lies in the urgency to help a patient in need, as such urgency sometimes precludes wearing proper PPE. [ 19 20 ] Finally, psychological stress, fatigue, and exhaustion can also preclude adherence to infection control measures, mainly PPEs.…”
Section: Discussionmentioning
confidence: 99%